BIAYA MEDIK LANGSUNG PASIEN STROKE NON-HEMORAGIK KELAS PERAWATAN 3 RSUD K.R.M.T WONGSONEGORO SEMARANG - Hanik Utaminingrum; Fef Rukminingsih (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The most common stroke in Indonesia is non-hemorrhagic stroke (SNH), which occurs in 85-87% of all stroke cases. Stroke requires expensive costs because the process of treating stroke patients is done in a long time and routine. SNH patients who go to K.R.M.T Wongsonegoro Hospital Semarang every year increase in number. This study aims to determine the amount of direct medical costs for treatment class 3 SNH patients at K.R.M.T Wongsonegoro Hospital Semarang and their compliance with Indonesian Case Based Groups (INA-CBG) rates. This study is a pharmacoeconomic study with a hospital perspective on direct medical costs using retrospective data for the October-December 2018 period. The object of this study is the medical record and billing data from the Hospital Information and Management System SNH patients participating in the National Health Insurance treated in treatment class 3. Based on the results of medical record tracking and billing data for SNH patients, 64 patients were known. The number of female patients was 41 people (64.06%). Most of the patients (93.75%) were over 45 years old. A total of 27 patients included in the category of mild SNH and 37 patients in the category of moderate SNH. The average direct medical cost for SNH patients in the mild category is IDR 3,005,019 ± 1,010,931, - and the compliance with INA-CBG’s tariff was 92.59%. The average direct medical cost for SNH patients in the moderate category is IDR 3,602,846 ± 1,259,001 and the compliance with INA-CBG rates of 94.59%.